Employment relations and dismissal regulations: Does employment legislation protect the health of workers?. (14th February 2019) - Barlow, Pepita; Reeves, Aaron; McKee, Martin; Stuckler, David
Abstract: Sociologists have long acknowledged that being in a precarious labour market position, whether employed or unemployed, can harm peoples' health. However, scholars have yet to fully investigate the possible contextual, institutional determinants of this relationship. Two institutions that were overlooked in previous empirical studies are the regulations that set minimum compensation for dismissal, severance payments, and entitlements to a period of notice before dismissal, notice periods. These institutions may be important for workers' health as they influence the degree of insecurity that workers are exposed to. Here, we test this hypothesis by examining whether longer notice periods and greater severance payments protect the health of labour market participants, both employed and unemployed. We constructed two cohorts of panel data before and during the European recession using data from 22 countries in the European Union Statistics on Income and Living Conditions (person years = 338, 000). We find more generous severance payments significantly reduce the probability that labour market participants, especially the unemployed, will experience declines in self‐reported health, with a slightly weaker relationship for longer notice periods.